Ag nanoparticle-decorated, ordered mesoporous silica as an efficient electrocatalyst for alkaline water oxidation reaction. Issue 6 (25th January 2019) - Kayal, Utpal; Mohanty, Bishnupad; Bhanja, Piyali; Chatterjee, Sauvik; Chandra, Debraj; Hara, Michikazu; Kumar Jena, Bikash; Bhaumik, Asim
Abstract : Ag NPs were decorated on the surface of a functionalized SBA-15 material and the resulting AgNPs@SBA-NH2 material showed excellent OER activity for electrochemical water oxidation under alkaline pH. Abstract : In recent years, several novel strategies for speeding up the slow kinetics of the water oxidation reaction have attracted considerable attention for generation of O2 . This is particularly important from the environmental perspective. Here we report a SBA-15 type, 2D-hexagonal functionalized mesoporous organosilica material as support for small Ag nanoparticles (NPs) by grafting the silica surface with 3-aminopropyltriethoxysilane, followed by chemical impregnation of Ag NPs at its surface, to obtain a AgNPs@SBA-NH2 material. The AgNPs@SBA-NH2 has been thoroughly characterized using several instrumental tools, such as powder X-ray diffraction, ultra-high resolution transition electron microscopy, N2 sorption, FT-IR spectroscopy, thermogravimetric and differential thermal analysis and X-ray photoelectron spectroscopy. High Brunauer–Emmett–Teller (BET) surface area and fine dispersion of Ag NPs throughout the surface of the amine-functionalized mesoporous material could enhance the rate of oxygen evolution reaction (OER) activity for AgNPs@SBA-NH2 in the electrochemical water splitting reaction.